Sensitivity of hemodynamic parameters to waveform, flow division, and head rotation in the human carotid bifurcation - Papaharilaou, Yannis; Seimenis, Ioannis; Anayiotos, Andreas (My University, 2009)
Hemodynamic parameters such as time averaged wall shear stress (TAWSS), wall shear stress temporal gradient (WSSTG) and Oscillatory Shear Index (OSI) have previously been cited as parameters associated with the development of atherosclerotic disease at the human carotid bifurcation [1,2]. The sensitivity of these important parameters however, with variations of driving flow waveform, flow division and posture changes are not well known. To investigate these changes, we have used image based CFD, to analyze the flowfield of the carotid bifurcation of a healthy volunteer for five different input waveforms, three flow division ratios and two head postures.
Keywords: Hemodynamics; Carotid artery